Salinomycin co-treatment enhances tamoxifen cytotoxicity in luminal A breast tumor cells by facilitating lysosomal degradation of receptor tyrosine kinases - Sommer, Ann-Katrin (Oncotarget, 2016)
Luminal A breast cancer is the most common breast cancer subtype which is usually treated with selective estrogen receptor modulators (SERMS) like tamoxifen. Nevertheless, one third of estrogen receptor positive breast cancer patients initially do not respond to endocrine therapy and about 40% of luminal A breast tumors recur in five years. In this study, we investigated an alternative treatment approach by combining tamoxifen and salinomycin in luminal A breast cancer cell lines. We have found that salinomycin induces an additional cytotoxic effect by inhibiting the ligand independent activation of ERα. Thereby salinomycin increases the intracellular calcium level. This leads to a premature fusion of endosomes with lysosomes and thus to the degradation of Egfr family members. Since this process is essential for luminal A breast cancer cells to circumvent tamoxifen treatment, the combination of both drugs induces cytotoxicity in tamoxifen sensitive as well as resistant luminal A breast cancer cell lines.